Commercial Bank Debt Restructuring : The Experience of Bulgaria - Houben, Aerdt (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1995)
This paper reviews commercial bank debt restructuring based on the recent experience of Bulgaria. While the deal is shown to have generated substantial debt relief at a remarkably low cost, several lessons are drawn that may be of broader relevance to countries restructuring bank debt. As, from time to time, it has been suggested that Bulgaria should have held out for more favorable treatment, or that it should now seek further debt reduction, the likely costs of these options are identified. Looking ahead, key policy issues are discussed that will determine growth prospects and debt sustainability over the medium term. It is argued that the deal's success remains to be underpinned in particular by judicious fiscal and debt management policies.